Psychiatric Disorders in Alzheimer Disease With the Presenilin-1 L226F Mutation. Issue 4 (December 2020) - Bartesaghi, Francesca; Rosci, Chiara Emilia; Rassiga, Cecilia; Barbieri, Valentina; Gambini, Orsola; Floro, Stefano; D'Arrigo, Andrea Maria; Del Sole, Angelo; Scarpini, Elio Angelo; Galimberti, Daniela; Priori, Alberto
Abstract : The presenilin-1 ( PSEN1 ) L226F mutation has been linked to very early onset of prominent behavioral and psychiatric disturbances followed by cognitive decline within a few years. We report a novel case of early-onset Alzheimer disease that was originally diagnosed as psychotic depression in a patient with this gene mutation. We also compare our patient's clinical data to those of other cases of this mutation that have been described in the literature. Because atypical behavioral and psychiatric disturbances in young (<40 years) individuals can herald Alzheimer disease, a tight collaboration between psychiatrists and neurologists is crucial for an early diagnosis.